A Philological Study of Kiai Zainullah’s Fatḥ al-Ghawāmiḍ: Its Contribution to the Scholarly Tradition of Pesantren - Muhammad Zamzami; Muhammad Hilal (Attanwir : Jurnal Keislaman dan Pendidikan, 2025)
This study explores the manuscript titled Fatḥ al-Ghawāmiḍ fī Sharḥ Kāfiya al-Farā’iḍ, written by Kiai Zainullah, a prominent Islamic scholar from Malang. The manuscript serves as a commentary on Kāfiya al-Farā’iḍ, a compilation of naẓm on Islamic inheritance law (‘ilm al-farā’iḍ), composed by the same author. Using a philological approach, this study analyzes the textual structure, content, and historical significance of Fatḥ al-Ghawāmiḍ, highlighting its role in the scholarly tradition of Indonesian pesantren. The study finds that the manuscript follows the classical method of Islamic scholarship, incorporating references to authoritative fiqh texts and employing a systematic explanatory style. Additionally, the work reflects the broader textual culture of pesantren, where the transmission of Islamic knowledge is maintained through the study of kitab kuning (classical Islamic texts). This research contributes to the understanding of Islamic legal manuscripts, especially on Islamic inheritance law, in Indonesia and emphasizes the importance of preserving the intellectual heritage of Nusantara scholars.